2008
DOI: 10.1080/17453670710015382
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of bone marrow aspirate for osteogenic repair using simple centrifugal methods

Abstract: Bone marrow transplantation can lead to osteogenic repair of intractable bone conditions. To achieve optimal clinical results, it is necessary to transplant as many cells with osteogenetic potential as possible. However, approaches involving special equipment and reagents for the extraction and purification of cells are expensive, and the complicated procedures involved are a hindrance to widespread acceptance of bone marrow transplantation for osteogenic repair. To standardize bone marrow transplantation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 5 publications
1
51
1
1
Order By: Relevance
“…We performed blood analysis according to the methods reported by Sakai et al [30]. The total amounts of bone marrow aspirate collected and transplanted were recorded.…”
Section: Blood Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We performed blood analysis according to the methods reported by Sakai et al [30]. The total amounts of bone marrow aspirate collected and transplanted were recorded.…”
Section: Blood Analysismentioning
confidence: 99%
“…A bone tunnel is created through the lateral cortex to reach the necrotic bone before transplantation of centrifugally concentrated bone marrow aspirate. Multipotent mesenchymal stem cells are found in bone marrow aspirate [29] and can be concentrated approximately 5-fold by centrifugation [30]. The osteogenic ability of bone marrow aspirate has been demonstrated in experiments using animal osteonecrosis models [31], and mesenchymal stem cells within bone marrow aspirate have been shown to directly differentiate into new bone [32].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, failed or delayed fracture healing and ONFH have been reported to be repaired with autologous bone marrow transplantation. Hernigou et al first reported the results of a prospective study on the benefits of autologous bone marrow transplantation [6, 7]. Moreover, Gangji et al first reported the results of a controlled, double-blind trial on the efficacy of autologous bone marrow transplantation [6].…”
Section: Introductionmentioning
confidence: 99%
“…The bone marrow is aspirated from the iliac crests, concentrated using a conventional manual blood bag centrifugation technique to extract buffy coats, and then injected into hips via drilling [7]. This procedure concentrates nucleated cells and platelets from clinical bone marrow aspirates (BMAs) to obtain osteogenic progenitor cells and growth factors for percutaneous transplantation to the necrotic area.…”
Section: Introductionmentioning
confidence: 99%
“…Core decompression [12], autologous bone grafts [13, 14], and bone marrow aspirate (BMA) transplantation [1518] have been performed in an attempt to regenerate necrotized bone. Core decompression is a method designed to improve blood flow into a necrotized lesion and aid the inflow of precursor cells or growth factors from normal tissues via communication between the necrotized lesion and normal tissues.…”
Section: Introductionmentioning
confidence: 99%